Can the CCCTB alleviate tax discrimination against loss-making European multinational groups? - Regina Ortmann; Caren Sureth (Arbeitskreis Quantitative Steuerlehre (arqus), 2014)
In March 2011, the European Commission submitted a proposal for a Council Directive on an optional common consolidated corporate tax base (CCCTB). If this proposed CCCTB system comes into force, taxes calculated under the currently existing system of separate accounting might be replaced by a system of group consolidation and formulary apportionment. Then, multinational groups (MNGs) would face the decision as to whether to opt for the CCCTB system. While prior research focuses mainly on the differences in economic behaviour under both systems in general, we study the conditions under which one or the other tax system is preferable from the perspective of an MNG, with a particular focus on loss offsets. We focus on European MNGs with losses at the parent and subsidiary level. While in our base model, the CCCTB proves to be attractive for temporarily loss-making MNGs, in our extended model we find mixed results. We identify four effects that determine the decision of an MNG: the tax-utilization of losses, the allocation of the tax base, the dividend and intragroup interest taxation. We find, e.g., that the CCCTB system proves advantageous for increasing loss/profit streams (e.g. from start-ups or R&D projects) of the individual group entities, whereas the system of separate accounting is beneficial for decreasing profit/loss streams (e.g. caused by a decrease in return from a mature product). The results of our analysis are helpful for MNGs facing the decision as to whether to opt for the CCCTB system. Moreover, our findings can support legislators and politicians in their tax reform discussions, as we provide information on the possible consequence of implementing this system on the expected decisions of corporate taxpayers that anticipate the tax effects of the CCCTB.
Keywords: H25; H21; 330; Loss-Offset; CCCTB; Separate Accounting; Investment Decisions